Closely related viruses of the marine picoeukaryotic alga Ostreococcus lucimarinus exhibit different ecological strategies. (13th May 2019) - Zimmerman, Amy E.; Bachy, Charles; Ma, Xiufeng; Roux, Simon; Jang, Ho Bin; Sullivan, Matthew B.; Waldbauer, Jacob R.; Worden, Alexandra Z.
Summary: In marine ecosystems, viruses are major disrupters of the direct flow of carbon and nutrients to higher trophic levels. Although the genetic diversity of several eukaryotic phytoplankton virus groups has been characterized, their infection dynamics are less understood, such that the physiological and ecological implications of their diversity remain unclear. We compared genomes and infection phenotypes of the two most closely related cultured phycodnaviruses infecting the widespread picoprasinophyte Ostreococcus lucimarinus under standard‐ (1.3 divisions per day) and limited‐light (0.41 divisions per day) nutrient replete conditions. OlV7 infection caused early arrest of the host cell cycle, coinciding with a significantly higher proportion of infected cells than OlV1‐amended treatments, regardless of host growth rate. OlV7 treatments showed a near‐50‐fold increase of progeny virions at the higher host growth rate, contrasting with OlV1's 16‐fold increase. However, production of OlV7 virions was more sensitive than OlV1 production to reduced host growth rate, suggesting fitness trade‐offs between infection efficiency and resilience to host physiology. Moreover, although organic matter released from OlV1‐ and OlV7‐infected hosts had broadly similar chemical composition, some distinct molecular signatures were observed. Collectively, these results suggest that current views on viral relatedness through marker and core gene analyses underplay operational divergence and consequences for host ecology.